The Effect Of Credibility, Electronic Word of Mouth Communication on Purchase Intentions - Septi Kurnia Prastiwi; Annisah Siti Aminah (Journal of Business and Management Review, 2021)
The purpose of this study is to analyze the EWOM (Electronic Word Of Mouth) factors, namely the credibility, quality, and quantity of EWOM that affect purchase intentions through the company's image on the @ Jilbrave.Official account. This type of research is quantitative research. The population used was Muslim women in Surakarta. The sampling technique was carried out using probability sampling methods. This study used a questionnaire as a data collection method with a sample of 133 respondents. Data were analyzed using the SPPS 22 program. This study used simple regression analysis. The independent variables in this study are credibility (X1), quality (X2), and quantity (X3) of EWOM, while the dependent variables are purchase intention (Y) and company image (M) as the mediating / intervening variables. The results of this study indicate that: (1) EWOM credibility has a significant effect on purchase intentions on the @ jilbrave.official account, (2) EWOM quality has no significant effect on purchase intentions on the @ jilbrave.official account, (3) EWOM quantity has a significant effect on intention. purchases on the @ jilbrave.official account, (4) EWOM credibility has a significant effect on the company's image on the @ jilbrave.official account, (5) EWOM quality has no significant effect on company image on @ jilbrave.official account, (6) EWOM quantity has a significant effect on the company image on the @ jilbrave.official account, (7) The credibility and quantity of EWOM have a significant effect on purchase intentions on the @ jilbrave.official account through the company's image.